1977
DOI: 10.1055/s-0028-1093536
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Glucagon-Like Immunoreactivity in a Pancreatectomized Patient

Abstract: True or 'pancreatic' glucagon-like immunoreactivity (GLI) was found in the plasma of a pancreatectomized patient. In contrast with the regulation of pancreatic GLI in normal controls, there was paradoxical release after oral glucose, no response to arginine or insulin-hypoglycaemia and somatostatin did not suppress its release, but tolbutamide did. Similar to controls, this pancreatic GLI appeared to be under adrenergic beta-receptor control. There was no apparent effect on blood glucose regulation despite mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The normalization and stabilization of blood glucose by a closed-loop system before our test may help to explain the difference in the effect of somatostatin. Nevertheless, the observations of Gerich et al 16 and Botha et al 24 failed to show a suppressive effect of somatostatin on blood glucose levels. However, in the first study, 16 the infusion of somatostatin, although it did not lower plasma glucose levels, induced an antihyperglycemic effect similar to our observations, since blood glucose remained stable during 2 h even though the last subcutaneous insulin injection had been administered 24 h previously, and control without SRIFwas not shown.…”
Section: Minutes Figure 3 Insulin Withdrawal In Four Pancreatectomizmentioning
confidence: 93%
See 1 more Smart Citation
“…The normalization and stabilization of blood glucose by a closed-loop system before our test may help to explain the difference in the effect of somatostatin. Nevertheless, the observations of Gerich et al 16 and Botha et al 24 failed to show a suppressive effect of somatostatin on blood glucose levels. However, in the first study, 16 the infusion of somatostatin, although it did not lower plasma glucose levels, induced an antihyperglycemic effect similar to our observations, since blood glucose remained stable during 2 h even though the last subcutaneous insulin injection had been administered 24 h previously, and control without SRIFwas not shown.…”
Section: Minutes Figure 3 Insulin Withdrawal In Four Pancreatectomizmentioning
confidence: 93%
“…Barnes and Bloom, 13 Villanueva et al, 19 and Muller et al 25 found that duodeno-pancreatectomized humans possess no circulating 3500-dalton glucagon, although Botha et al 24 claimed to have detected some. Tiengo et al 62 found the glucagon immunoreactivity was precipitated by ethanol, suggesting that it was essentially related to big plasma glucagon.…”
Section: Minutes Figure 3 Insulin Withdrawal In Four Pancreatectomizmentioning
confidence: 96%
“…These metabolic features may repre- sent a pattern diametrically opposite to that described in the glucagonoma syndrome [39]. Six other studies, however, have documented the presence of IRG or glucagon-like immunoreactivity in plasma from pancreatectomized patients (a total of 13 subjects) and from some groups of patients with chronic pancreatitis [31,40,44]; the 30 K antiserum was used in most of these reports and plasma samples were submitted to various extraction procedures in three studies [31,42,43]. However plasma IRG was not increased by arginine [42, 431, adrenaline [42] or cessation of insulin therapy [43]; it was paradoxically increased by oral glucose or meals [43].…”
Section: Discussionmentioning
confidence: 99%